Invasive fungal infections in paediatric acute myeloid leukaemia. Issue 4 (26th February 2013) - Johnston, D. L.; Lewis, V.; Yanofsky, R.; Gillmeister, B.; Ethier, M. C.; Mitchell, D.; Cellot, S.; Dix, D.; Portwine, C.; Price, V.; Silva, M.; Zelcer, S.; et al.
Summary Invasive fungal infections (IFIs) are a major cause of morbidity and mortality in paediatric acute myeloid leukaemia (AML). This study describes risk factors for IFI and IFI‐related sepsis in this population. We conducted a population‐based, retrospective cohort study of children with AML in Canada. IFIs during chemotherapy and prior to haematopoietic stem cell transplantation, relapse, persistent disease or death were identified. Risk factors for proven or probable IFI were examined. Among courses complicated by IFI, risk factors for sepsis were also evaluated. There were 341 children with AML included of which 41 (12.0%) experienced 46 different episodes of IFI. Candida species accounted for 23 (50.0%) of IFIs and Aspergillus spp. accounted for 14 (30.4%). Days of broad‐spectrum antibiotics, days of corticosteroids and neutropenia at start of the course were independently associated with IFI. Only days of fever were independently associated with IFI‐related sepsis. Invasive fungal infections occurred in 12.0% of paediatric AML patients. Risk factors for IFI and IFI‐related sepsis were identified. This knowledge may help to consider targeted strategies.